2015
DOI: 10.5194/acp-15-12465-2015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the CMAM30 data set with ACE-FTS and OSIRIS: polar regions

Abstract: Abstract. CMAM30 is a 30-year data set extending from 1979 to 2010 that is generated using a version of the Canadian Middle Atmosphere Model (CMAM) in which the winds and temperatures are relaxed to the Interim Reanalysis product from the European Centre for Medium-Range Weather Forecasts (ERA-Interim). The data set has dynamical fields that are very close to the reanalysis below 1 hPa and chemical tracers that are self-consistent with respect to the model winds and temperature. The chemical tracers are expect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This study uses hindcast specified-dynamics reference simulations (RefC1SD) (Plummer et al, 2014) conducted for the Chemistry Climate Model Initiative (CCMI-1) (Hegglin and Lamarque, 2015;Morgenstern et al, 2017), of both ozone (O 3 ) and stratosphere-tagged tracer ozone (O 3 S) for the period 1980-2010 inclusive from two state-of-theart CCMs: European Centre for Medium-Range Weather Forecasts -Hamburg (ECHAM)/Modular Earth Submodel System (MESSy) Atmospheric Chemistry (EMAC;Jöckel et al, 2016) and the Canadian Middle Atmosphere Model (CMAM; Scinocca et al, 2008). These two models were primarily selected due to the close similarity in the O 3 S tracer definition (detailed below in Sect.…”
Section: Ccm Simulationsmentioning
confidence: 99%
“…This study uses hindcast specified-dynamics reference simulations (RefC1SD) (Plummer et al, 2014) conducted for the Chemistry Climate Model Initiative (CCMI-1) (Hegglin and Lamarque, 2015;Morgenstern et al, 2017), of both ozone (O 3 ) and stratosphere-tagged tracer ozone (O 3 S) for the period 1980-2010 inclusive from two state-of-theart CCMs: European Centre for Medium-Range Weather Forecasts -Hamburg (ECHAM)/Modular Earth Submodel System (MESSy) Atmospheric Chemistry (EMAC;Jöckel et al, 2016) and the Canadian Middle Atmosphere Model (CMAM; Scinocca et al, 2008). These two models were primarily selected due to the close similarity in the O 3 S tracer definition (detailed below in Sect.…”
Section: Ccm Simulationsmentioning
confidence: 99%
“…Their quality has been extensively evaluated in numerous data characterization and validation papers (i.e. Pumphrey et al, 2007;Read et al, 2007;Santee et al, 2007;Schwartz et al, 2008;Stiller et al, 2012;Hegglin et al, 2013;Raspollini et al, 2013;Neu et al, 2014;Livesey et al, 2017;Sheese et al, 2017). Furthermore, their longterm stability has also been studied (i.e.…”
Section: Millán Et Al: Sampling and Screening Biasesmentioning
confidence: 99%
“…Extensive validation (de Grandpré et al, 2000;Hegglin and Shepherd, 2007;Melo et al, 2008;Jin et al, 2005Jin et al, , 2009 has shown that the free-running version of this model performs well against observations relevant to dynamics, transport, and chemistry. Comparisons against ACE-FTS and the Odin Optical Spectrograph and Infrared Imaging System (OSIRIS) have shown that CMAM30-SD has a good representation of stratospheric temperature, H 2 O, O 3 , and CH 4 in polar regions (Pendlebury et al, 2015). Further, CMAM30-SD has been used to construct a long-term H 2 O record, acting as a transfer function between satellite observations (Hegglin et al, 2014), and it reproduces halogen-induced mid-latitude O 3 depletion sufficiently well to be used in longterm O 3 trend studies (Shepherd et al, 2014).…”
Section: Millán Et Al: Sampling and Screening Biasesmentioning
confidence: 99%
“…Extensive validation (de Grandpré 5 et al, 2000;Hegglin and Shepherd, 2007;Melo et al, 2008;Jin et al, 2005Jin et al, , 2009 has shown that the free-running version of this model performs well against observations relevant to dynamics, transport, and chemistry. Comparisons against ACE-FTS and the Odin Optical Spectrograph and Infrared Imaging System (OSIRIS) have shown that CMAM30-SD has a good representation of stratospheric temperature, H 2 O, O 3 , and CH 4 in polar regions (Pendlebury et al, 2015). Further, CMAM30-SD has been used to construct a long-term H 2 O record, acting as a transfer function between satellite observations (Hegglin 10 et al, 2014), and it reproduces halogen-induced midlatitude O 3 depletion sufficiently well to be used in long-term O 3 trend studies .…”
Section: Model Fieldsmentioning
confidence: 99%